1993
DOI: 10.1017/s0022215100123618
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors involved in stomal recurrence following laryngectomy

Abstract: Stomal recurrence after surgery for laryngeal tumours is an extremely serious complication, with a dismal prognosis despite aggressive surgical therapy or high-dose irradiation. Data from 209 patients who underwent total laryngectomy for cancers of the larynx and hypopharynx were retrieved from the registry of the Department of Otorhinolaryngology at the Hospital ‘Virgen de las Nieves’ of Granada. Stomal recurrence developed in 8.1 per cent of them (17 cases). We analysed several parameters from each case: fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Many of these tumors that cause upper ai- rway obstruction also extend towards the subglottis. Prior tracheostomy in these patients, necessary to establish a new airway has been identified as an important risk factor for recurrences in the tracheostoma area 1,7,19 . This is due to the fact that prior tracheostomy may allow the implantation of viable neoplastic cells from tumor shedding that have an intense inflammatory process and repair granulation tissue -the bed may be prone to cell adhesion.2 In the literature such risk is reported as varying between 8 and 41% 1,6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these tumors that cause upper ai- rway obstruction also extend towards the subglottis. Prior tracheostomy in these patients, necessary to establish a new airway has been identified as an important risk factor for recurrences in the tracheostoma area 1,7,19 . This is due to the fact that prior tracheostomy may allow the implantation of viable neoplastic cells from tumor shedding that have an intense inflammatory process and repair granulation tissue -the bed may be prone to cell adhesion.2 In the literature such risk is reported as varying between 8 and 41% 1,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Another significant factor that may cause difficulties in analyzing recurrence incidence in the tracheostoma area is the number of synonyms used to describe such pathology, such as: tracheal metastasis, peritracheal recurrence, tracheal recurrence, paratracheostomal tumor, tracheostomal metastasis, second primary tumor in the trachea 3 . Most relapses in the tracheostoma area are diagnosed in the first year after total laryngectomy and its pathogeny is still not clearly defined 1,[4][5][6][7] . Tumor site and disease staging, infraglottic invasion, previous tracheostomy, insufficient surgical margins after total laryngectomy, thyroid invasion by the laryngeal tumor, tumoral implants during surgery and paratracheal lymphnode metastasis are the most mentioned correlated factors in the literature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed in this paper we have not attempted to distinguish between these particular types and classify all stomal/peri-stomal recurrences as LR. Patients presenting with local recurrence have a dismal outcome with approximately 50 % presenting in the first year after completion of treatment [3,4] and 80 % dying in the first 2 years after completion of treatment [19].…”
Section: Discussionmentioning
confidence: 99%
“…The latter technique has largely been abandoned [1] and there has been a move away from pre-operative tracheostomy (POT) towards TOL in recent years. This move has been driven by studies which showed that POT was associated with a higher risk of stomal/peristomal recurrence [2][3][4][5], and that TOL could reliably secure the airway [6].…”
Section: Introductionmentioning
confidence: 99%